Analisis Dan Perancangan Sistem Informasi Pengelolaan Bantuan Pangan Non Tunai (BPNT) Berbasis Web Pada Pelaksanaan Distribusi BPNT Di Desa Lubuk Napal - Ichsandi, Ichsandi; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2020)
Desa Lubuk Napal in distribution Bantuan Pangan Non Tunai (BPNT) still get trouble, such as : An error occurs in the distribution of the aid , the process of making the report for the reception of bpnt took quite some time for , and data pengeloaan rice stocks and eggs which are distributed sometimes an error occurs in recording and calculation. The purpose of research is analyzing and design information systems processing Bantuan Pangan Non Tunai (BPNT) web-based using PHP programming language and MySQL database. Metodology of this research use waterfall model and unified model language using use case diagram, activity diagram, and class diagram. Conclusion of this system can process data of distribution to check recipients with no. Id card that will not be the double and there have been wrong in the distribution of, and can print reports required by the center of marl village in the distribution of the reports on the recipients are: bpnt bpnt, report, aid supplies reports revenue and reports on the distribution of aid.